2020 16th International Conference on Network and Service Management (CNSM) 2020
DOI: 10.23919/cnsm50824.2020.9269102
|View full text |Cite
|
Sign up to set email alerts
|

BGP Anycast Tuner: Intuitive Route Management for Anycast Services

Abstract: IP anycast has become a vital technology for DNS and CDN operators alike. Yet, while big operators have their tools to monitor and configure anycast routing, most of anycast networks are still configured manually. In this paper, we introduce a new approach to anycast management. Our solution is based on active measurements combined with traffic engineering. We propose the concept of a "BGP Cookbook" that allows operators to forecast the effects of routing policy changes over their services. We also introduce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 41 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…It plays a vital role for DNS and CDN and services, but different issues have been noted, including the detection latency of IP anycast prefixes [20], AS-level anycast path inflation [21], and client-server mapping limitations that arise in CDN routing [2]. Several enhancements have been discussed focusing on either performance, see, e.g., [22,23], or security, e.g., to mitigate distributed denial-of-service (DDoS) attacks [5]. It has been shown that anycast routing can achieve near-optimal response times and that it can be tailored to suit the QoS requirements of DiffServ networks [24], but these techniques often require knowledge about the global network state (i.e., router loads) [25,26].…”
Section: Related Workmentioning
confidence: 99%
“…It plays a vital role for DNS and CDN and services, but different issues have been noted, including the detection latency of IP anycast prefixes [20], AS-level anycast path inflation [21], and client-server mapping limitations that arise in CDN routing [2]. Several enhancements have been discussed focusing on either performance, see, e.g., [22,23], or security, e.g., to mitigate distributed denial-of-service (DDoS) attacks [5]. It has been shown that anycast routing can achieve near-optimal response times and that it can be tailored to suit the QoS requirements of DiffServ networks [24], but these techniques often require knowledge about the global network state (i.e., router loads) [25,26].…”
Section: Related Workmentioning
confidence: 99%
“…The contributions of this chapter include a methodology to anticipate the impact of a major IXP outage, and the formulation of novel metrics that allow for the assessment of IXPs in terms of coverage, hegemony, and regional representation. The study discussed in this chapter was published as a research paper in an academic conference [42].…”
Section: Discussionmentioning
confidence: 99%
“…In Network Traffic Measurement and Analysis Conference (TMA), pages 1-9, Sept. 2021. ISBN 9783903176270 [42].…”
Section: Chapter 5 -Peering Anycast At Ixpsmentioning
confidence: 99%
See 2 more Smart Citations